1998
DOI: 10.1056/nejm199801153380304
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-2–Receptor Blockade with Daclizumab to Prevent Acute Rejection in Renal Transplantation

Abstract: Daclizumab reduces the frequency of acute rejection in kidney-transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
324
3
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 855 publications
(342 citation statements)
references
References 18 publications
14
324
3
1
Order By: Relevance
“…In studies with human mixed lymphocyte reactions, MPA inhibits IL-2 R and transferrin R expression after 6 days of culture, but ineffectively inhibits IL-2 R or transferrin R expression after 3 days of culture (42). Since IL-2 R, LFA-1 or ICAM-1 on T cells are targets for therapeutic antibodies used to suppress rejection, suppression of their expression by MMF treatment emphasizes their important role in allograft rejection (43)(44)(45)(46)(47).…”
Section: Pharmacodynamics Of Mycophenolate Mofetilmentioning
confidence: 99%
“…In studies with human mixed lymphocyte reactions, MPA inhibits IL-2 R and transferrin R expression after 6 days of culture, but ineffectively inhibits IL-2 R or transferrin R expression after 3 days of culture (42). Since IL-2 R, LFA-1 or ICAM-1 on T cells are targets for therapeutic antibodies used to suppress rejection, suppression of their expression by MMF treatment emphasizes their important role in allograft rejection (43)(44)(45)(46)(47).…”
Section: Pharmacodynamics Of Mycophenolate Mofetilmentioning
confidence: 99%
“…The use of humanized or chimeric monoclonal antibodies against the IL-2 receptor has resulted in decreased incidence of rejection without an apparent increase in infection or lymphoproliferative disease [11,12] as compared with anti lymphocyte globulin or anti thymocyte globulin. These drugs have been used in patients who have a higher chances of acute rejection like poorly matched patients and children.…”
Section: Discussionmentioning
confidence: 99%
“…Two major phase III studies were used to evaluate the clinical efficacy of daclizumab linked to immunosuppression compared with a placebo with the same immunosuppressive regimen (Vincenti et al, 1998;Nashan et al, 1999). In the two phase III multicenter studies, which were double-blind and randomized, the end points were the incidence of biopsy-proven rejection that occurred in the first 6 months after transplantation.…”
Section: Daclizumab Therapy For Patients Receiving Organ Allograftsmentioning
confidence: 99%
“…This discordance in IL-2R alpha expression between normal cells, which we wish to retain that do not express the receptor, and abnormal cells in disease that express the receptor provided the scientific basis for the use of anti-Tac and its humanized form, daclizumab, for an array of clinical conditions including CD25-expressing leukemias and lymphomas, autoimmune diseases and to prevent allograft rejection. In 1997 daclizumab, the humanized form of this antibody was approved by the FDA for use in the prevention of renal allograft rejection (Vincenti et al, 1998;Wiseman and Faulds, 1999). In addition, we and our collaborators demonstrated that daclizumab is of value in the treatment of patients with non-infectious uveitis, multiple sclerosis and the neurological disease, human T-cell lymphotropic virus I (HTLV-I)-associated myelopathy (HAM)/TSP (Lehky et al, 1998;Nussenblatt et al, 1999;Bielekova et al, 2004).…”
Section: Introductionmentioning
confidence: 99%